INTERACTION OF STOCKING DENSITY AND DIFFERENT PLANT TYPES IN CULTIVATING SANGKURIANG CATFISH (Clarias gariepinus var. Sangkuriang) AQUAPONIC TECHNOLOGY - Dg. Masese, Risa Apriana A.; Ndobe, Samliok; Widiastuti, Irawati Mei (AQUASAINS, 2024)
This study investigated the impact of varying stocking densities and plant species interactions within an aquaponic framework. Conducted over a 45-day period (August-October 2023) at the Experimental Farm of Tadulako University, Palu, Central Sulawesi, the research utilized juvenile Sangkuriang catfish (Clarias gariepinus var. Sangkuriang) as the focal organism. Employing a factorial design, with stocking densities 12, 20, and 28 fish per 40 liters of water and three distinct plant species (Ipomoea aquatica, Brassica rapa subsp. chinensis, and Lactuca sativa), the study aimed to elucidate optimal growth conditions. Key findings revealed that the stocking density of 12 fish per 40 liters of water, coupled with pakchoi plants, yielded the most significant growth enhancements. Specifically, this configuration demonstrated a specific growth rate of 6.66±0.7% and absolute weight growth of 14.06±1.0, along with a specific length growth rate of 2.10±0.6% and absolute length growth of 4.48±0.6%. Notably, water quality parameters remained within acceptable limits across all treatments, ensuring an environment conducive to catfish growth. In conclusion, this research underscores the critical role of stocking density and plant selection in optimizing aquaponic systems. The findings offer valuable insights into enhancing both fish and plant growth dynamics within integrated aquaponic frameworks. Keywords: Catfish farming, aquaponics, growth rate, survival rate.